Glycogen Phosphorylase, the Product of the glgP Gene, Catalyzes Glycogen Breakdown by Removing Glucose Units from the Nonreducing Ends in Escherichia coli - Alonso-Casajús, Nora (American Society for Microbiology, 2006)
To understand the biological function of bacterial glycogen phosphorylase (GlgP), we have produced and characterized Escherichia coli cells with null or altered glgP expression. glgP deletion mutants (ΔglgP) totally lacked glycogen phosphorylase activity, indicating that all the enzymatic activity is dependent upon the glgP product. Moderate increases of glycogen phosphorylase activity were accompanied by marked reductions of the intracellular glycogen levels in cells cultured in the presence of glucose. In turn, both glycogen content and rates of glycogen accumulation in ΔglgP cells were severalfold higher than those of wild-type cells. These defects correlated with the presence of longer external chains in the polysaccharide accumulated by ΔglgP cells. The overall results thus show that GlgP catalyzes glycogen breakdown and affects glycogen structure by removing glucose units from the polysaccharide outer chains in E. coli.